Antiamnesic and antioxidants effects of ferulago angulata essential oil against scopolamine-Induced memory impairment in laboratory rats - Hritcu, Lucian; Bağcı, Eyüp; Akbaba, Emel Aydın; Mihasan, Marius (My University, 2015)
Ferulago angulata (Apiaceae) is a shrub indigenous to western Iran, Turkey and Iraq. In traditional medicine, F. angulata is recommended for treating digestive pains, hemorrhoids, snake bite, ulcers and as sedative. In the present study, the effects of inhaled F. angulata essential oil (1 and 3 %, daily, for 21 days) on spatial memory performance were assessed in scopolamine-treated rats. Scopolamine-induced memory impairments were observed, as measured by the Y-maze and radial arm-maze tasks. Decreased activities of superoxide dismutase, glutathione peroxidase and catalase along with increase of acetylcholinesterase activity and decrease of total content of reduced glutathione were observed in the rat hippocampal homogenates of scopolamine-treated animals as compared with control. Production of protein carbonyl and malondialdehyde significantly increased in the rat hippocampal homogenates of scopolamine-treated animals as compared with control, as a consequence of impaired antioxidant enzymes activities. Additionally, in scopolamine- treated rats exposure to F. angulata essential oil significantly improved memory formation and decreased oxidative stress, suggesting memory-enhancing and antioxidant effects. Therefore, our results suggest that multiple exposures to F. angulata essential oil ameliorate scopolamine-induced spatial memory impairment by attenuation of the oxidative stress in the rat hippocampus
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Ethical standard This study was approved by the Committee on the Ethics of Animal Experiments of the Alexandru Ioan Cuza University of Iasi (Permit Number: 2192) and also, efforts were made to minimize animal suffering and to reduce the number of animals used.
Keywords: Alzheimer’s disease; Ferulago angulata essential oil; Spatial memory; Oxidative stress